A study on environmental awareness among youth in College of Technology Malacca Branch / Nur Rabeatul Adawiah Razali and Nurul Nabilah Mohd Aziz - Razali, Nur Rabeatul Adawiah; Mohd Aziz, Nurul Nabilah (Faculty of Administrative Science and Policy Studies, 2013)
Environment awareness is a complex and wide-problem which is faced by the people in the world including Malaysia society. There have been reported that the awareness among the youth in Malaysia is still in the low rate. Generally, with the greater awareness from the people, there would be not many environmental problems or issues. Although environmental awareness is building up in Malaysia, the past decade of rapid economic growth and industrialization has caused serious environmental challenges in Malaysia. The lack of awareness among the youth may due to insufficient understanding of long-term consequences of pollution and environment deterioration. Based on these issues, this study was conducted to determine the environment awareness among youth in College of Technology Malacca Branch by specifically focused on the youth in the institutions. A sample of 160 respondents was involved in this study. However, only 137 questionnaires were received. The main objective of this study is to determine the contributing factor that lead towards youth environmental awareness. The factors identified are youth attitudes, mass media, and education. The statistical techniques used in this study are Descriptive Statistic, Regression Analysis, and Spearmen Correlation. This study revealed that the most contributing factor that leads to youth environmental awareness is mass media. Meanwhile, youth’s environmental awareness is also influence by attitude and education (positive relationship). Therefore, several recommendations are provided in order to strengthen the role of mass media and education in promoting environmental awareness among youth.